Tightening the requirements for species diagnoses would help integrate DNA-based descriptions in taxonomic practice. - Frank E Rheindt; Patrice Bouchard; Richard L Pyle; Francisco Welter-Schultes; Erna Aescht; Shane T Ahyong; Alberto Ballerio; Thierry Bourgoin; Luis M P Ceríaco; Dmitry Dmitriev; Neal Evenhuis; Mark J Grygier; et al. (PLoS Biology, 2023)
Modern advances in DNA sequencing hold the promise of facilitating descriptions of new organisms at ever finer precision but have come with challenges as the major Codes of bionomenclature contain poorly defined requirements for species and subspecies diagnoses (henceforth, species diagnoses), which is particularly problematic for DNA-based taxonomy. We, the commissioners of the International Commission on Zoological Nomenclature, advocate a tightening of the definition of "species diagnosis" in future editions of Codes of bionomenclature, for example, through the introduction of requirements for specific information on the character states of differentiating traits in comparison with similar species. Such new provisions would enhance taxonomic standards and ensure that all diagnoses, including DNA-based ones, contain adequate taxonomic context. Our recommendations are intended to spur discussion among biologists, as broad community consensus is critical ahead of the implementation of new editions of the International Code of Zoological Nomenclature and other Codes of bionomenclature.